Cardiorenal syndrome in patients with rheumatoid arthritis - Z. Yu. Mutovina; A. I. Zagrebneva; E. A. Galushko; A. V. Gordeev (Современная ревматология)
In 2008, the term cardiorenal syndrome (CRS) was proposed by the Acute Dialysis Quality Initiative (ADQI) Group to denote pathological reciprocal conditions involving the heart and kidneys, which develop due to acute or chronic dysfunction of one of the organs, followed by acute or chronic dysfunction of the other one. The problem of CRS in patients with rheumatoid arthritis (RA) has not been studied. Of the greatest interest is CRS type 5 or secondary CRS that occurs in patients with systemic diseases, including in those with RA. Currently, there is no doubt that the risk of developing cardiovascular diseases in RA patients and the prevalence of non-ischemic and ischemic chronic heart failure (CHF) are higher than those in the general population. There is evidence that the prevalence of chronic kidney disease (CKD) and renal pathology-associated cardiovascular risk factors (RF) is high in patients with RA. In addition to traditional RFs for cardiovascular and kidney diseases, autoimmune inflammation is an independent predictor for CHF and CKD. The characteristics of CRS in RA should be investigated to develop an effective treatment strategy for this category of patients.